Prognostic impact of renal function trajectories and temporal variability amongst anticoagulated atrial fibrillation patients: a subgroup analysis of the SPORTIF III and V trials. (25th November 2020) - Proietti, M; Gumprecht, J; Romiti, G.F; Lip, G.Y.H
Abstract: Background: Renal function is a major determinant of major adverse outcomes in patients with atrial fibrillation (AF). Scarce data are available about the impact of renal function trajectories and creatinine clearance (CrCl) temporal variability, on prognosis. Aim: To evaluate the progression and impact of renal function impairment and variability on outcomes over a long-term follow-up observation in a cohort of anticoagulated AF patients. Methods: We included warfarin-treated AF patients in SPORTIF trials with available creatinine clearance (according to Cockroft-Gault) at baseline and at least 4 evaluations throughout their follow-up. Patients with a BMI ≥45 kg/m 2 were excluded from the analysis. Average successive variability (ASV) was used as measure of variability. Results: Among 3665 original patients, 3366 (91.8%) were included in this analysis. Median [IQR] CHA2DS2-VASc score was 3 [2–4] and HAS-BLED was 3 [2–4]. At baseline, 876 (26.0%) patients had CKD (CrCl <60 mL/min), with 14 (0.4%) patients having severe CKD (<30 mL/min), with a mean (SD) CrCl of 86.7 (47.4) mL/min. Over a mean (SD) 577.1 (122.1) days of follow-up, a total of 521 new CKD cases were found with an overall incidence of 13.1 per 100 patient-years, with 91 new severe CKD cases (1.71 per 100 patient-years). Across follow-up, prevalence of CKD and severe CKD increased progressively (both p<0.001) [Figure]. Mean (SD) AVS was −0.567 (±2.803) mL/min. According to AVS, patients were divided into quartiles: i) Q1: +34.012/+0.450; ii) Q2: +0.449/−0.443; iii) Q3: −0.443/−1.503; Q4: −1.505/−19.750. While no difference was found in stroke/systemic embolism, rate of major bleeding was higher in Q4 (4.5%) and Q1 (4.0%) than in other quartiles (Q2 2.5%, Q3 2.0%; p=0.009) as well as all-cause death (Q4: 6.7%; p=0.003 compared to other quartiles). A Cox multivariate adjusted model documented that AVS Q1 and Q4 were independently associated with a higher risk of major bleeding, while Q4 was associated with a higher risk of all-cause death (Table). Conclusion: In a cohort of AF patients treated with warfarin, characterized by a progressive increase in the proportion with CKD and severe CKD, the largest reduction in CrCl throughout follow-up was associated to an increased risk of major bleeding and all-cause death. Funding Acknowledgement: Type of funding source: None